Effect of Working Capital Management on the Profitability of Manufacturing Firms: Evidence from Treveni Industries, Nepal - Tiwari, Uday Kishor; Duwadi, Raju; Tiwad, Ram Kumar (Journal of Nepal Commerce Association, 2025)
Working capital management (WCM) is a crucial determinant of a firm’s financial stability and profitability, as it focuses on the efficient management of short-term assets and liabilities to ensure adequate liquidity for daily operations. This study examines the impact of WCM on the profitability of Nepal’s manufacturing sector, using Treveni Industries Pvt. Ltd. as a case study, with specific focus on the Contech Concrete and allied industry. A descriptive research design is employed, and the analysis is supported by clearly presented tables. Secondary data were collected from audited financial statements of Treveni Industries Pvt. Ltd., along with relevant research articles, journals, and industry reports. The findings reveal that increases in the Inventory Turnover Ratio, Average Collection Period, Debt Ratio, and Current Ratio are associated with a decline in Return on Equity, whereas improvements in the Average Payment Period and Cash Conversion Cycle show a positive relationship with profitability indicators such as ROE and ROA. Overall, the study concludes that effective working capital management significantly influences profitability, accounting for approximately 25% of variations in industry profits.